1968
DOI: 10.1128/jb.95.3.801-810.1968
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bacterial Flagella I. Requirement for Protein and Ribonucleic Acid Synthesis During Flagellar Regeneration in Bacillus subtilis

Abstract: A relatively simple immunochemical procedure for estimating flagellar protein was developed. This procedure involved measuring the binding of purified, radioactively labeled, antiflagellar antibodies to bacteria. The assay was used to determine the requirements for ribonucleic acid (RNA) and protein synthesis during flagellar regeneration in Bacillus subtilis. Immediate inhibition of flagella development was observed when chloramphenical or puromycin was added to cells. This inhibition indicated the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These are functional and physical properties characteristic of mRNA. A similar requirement for RNA synthesis during flagellar regeneration in B. subtilis has recently been demonstrated by Dimmitt et al (6).…”
Section: Discussionsupporting
confidence: 78%
“…These are functional and physical properties characteristic of mRNA. A similar requirement for RNA synthesis during flagellar regeneration in B. subtilis has recently been demonstrated by Dimmitt et al (6).…”
Section: Discussionsupporting
confidence: 78%
“…Samples (I ml) were taken and treated as described in Materials and Methods. Symbols: 0, vegetative-cell control; A, vegetative cells plus 8 were incubated in DCT medium at 3.1 X 108 cells/ml, andL-keucine-1-14C (24.3 mc/mmole) was added at 0.05 uc/ml. Samples (2 ml) were taken and treated as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Radioactive RNA was extracted from cultures of RCstr and RCrel bacteria which had been pulse labeled either during exponential growth or during amino acid starvation. The results indicated that, under the two conditions, the fraction of the labeled RNA which could be characterized as mRNA by hybrid formation with DNA was essentially the same; i.e., 20 to 25% of the labeled RNA was hybridizable. Since the fraction of the labeled RNA that was characterized as mRNA seemed to be constant under all conditions, these results also support the hypothesis that the regulation of RNA synthesis is coordinate.…”
Section: Coordinate Regulation Of Rna Synthesismentioning
confidence: 95%
“…The conclusion that mRNA synthesis can continue during amino acid starvation was also arrived at from measurements of flagellar protein formation in B. subtilis and S. typhimurium during tryptophan starvation (20). Flagellar protein contains no tryptophan residues, so that it is possible to study its formation in cells that are tryptophan starved.…”
Section: Downloaded Frommentioning
confidence: 99%